THE LEGAL POSITION OF THE RUSSIAN FEDERATION IN RELATION TO THE OUTER LIMITS OF THE CONTINENTAL SHELF IN THE ARCTIC ... - SHEPELEV, DENIS; SHUSTOV, GLEB (LLC «MIAS Expert», 2021)
This article examines the question of the ownership of the outer limits of the continental shelf and issues related to the legal justification for the assignment of these territories to the Russian Federation. The relevance of this topic is related to the growing interest of the Nordic countries in the Arctic territories in connection with the melting of ice and the opening of new trade routes, this interest is also justified by the economic factor. The main purpose of the work will be the correlation of scientific concepts, consideration of the legal justification for the ownership of the continental shelf in the Arctic of the Russian Federation, analysis of the legal position of the Russian Federation in relation to the application to the Commission on the Limits of the Continental Shelf. The key problem of the article is the correlation of the established scientific Russian and foreign concepts about the legal status of the Arctic, the identification of supporters of a fair approach that allows the Arctic ...